Potential Chronotherapeutic Optimization of Antimalarials in Systemic Lupus Erythematosus: Is Toll-Like Receptor 9 Expression Dependent on the Circadian Cycle in Humans? - Martínez-García, Erika Aurora; Zavala-Cerna, Maria Guadalupe; Lujano-Benítez, Andrea Verónica; Sánchez-Hernández, Pedro Ernesto; Martín-Márquez, Beatriz Teresita; Sandoval-García, Flavio; Vázquez-Del Mercado, Mónica (Frontiers in Immunology, 2018)
Toll-Like Receptor 9 (TLR9) belongs to the group of endosomal receptors of the innate immune system with the ability to recognize hypomethylated CpG sequences from DNA. There is scarce information about TLR9 expression and its association with the circadian cycle (CC). Different patterns of TLR9 expression are regulated by the CC in mice, with an elevated expression at Zeitgeber time (ZT) 19 (1:00 am); nevertheless, we still need to corroborate this in humans. In systemic lupus erythematosus (SLE), the inhibitory effect of chloroquine (CQ) on TLR9 is limited. TLR9 activation has been associated with the presence of some autoantibodies: anti-Sm/RNP, anti-histone, anti-Ro, anti-La, and anti-dsDNA. Treatment with CQ for SLE has been proven to be useful, in part by interfering with HLA-antigen coupling and with TLR9 ligand recognition. Studies have shown that TLR9 inhibitors such as antimalarial drugs (AMDs) are able to mask TLR9-binding sites on nucleic acids. The data presented here provides the basic information that could be useful for other clinical researchers to design studies that will have an impact in achieving a chronotherapeutic effect by defining the ideal time for CQ administration in SLE patients, consequently reducing the pathological effects that follow the activation of TLR9.